Isolation and identification of some gram-negative bacteria from cockroaches collected from hospital, restaurant and slum areas of Dhaka city, Bangladesh - Akter, T; Ahmed, S; Biswas, R (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The study was conducted to identify the bacteriological quality from different species of cockroaches in three study areas in Dhaka city. A total of 15 cockroaches was collected from three different selected study areas, viz. Penang Restaurant of Bakshi Bazar, Sir Salimullah Medical College Mitford Hospital and Urban slum of Kamalapur, Dhaka. Using detection keys, the cockroaches were identified as Periplaneta americana (53.33%), Blatella germanica (40%) and Blatta orientalis (6.67%). All of 15 cockroaches were used to isolate bacteria from external body surface and alimentary tract. A total of 48 isolates was obtained from these three species of cockroaches. Out of them 29 (60.42%) isolates were obtained from P. americana, 17 (35.42%) from B. germanica, and 2 (4.16%) from B. orientalis. Three Gram negative bacteria, viz. Klebsiella sp., Escherichia coli and Pseudomonas sp. were isolated from alimentary canal and external surface. On the external body surface 71.43% isolates were E. coli, 21.43% were Pseudomonas sp. and 7.14% were Klebsilella sp. In case of alimentary tract, 55.89% isolates were Pseudomonas sp., 23.52% were E. coli, and the rest 20.59% were Klebsiella sp. Comparison between study areas showed that the food handling area yielded maximum number (41.67%) of isolates and the urban slum yielded minimum number (25%) of isolates. In food handling isolates, 45% were Klebsiella, whereas E. coli and Pseudomonas sp. were 40% and 15%, respectively. In Hospital, E. coli was the most common (50%), followed by Klebsiella (37.5%) and Pseudomona sp. (12.50%). In urban slum, 41.67% isolates were Klebsiella sp., 41.67% were Pseudomonas sp. and 16.66% were E. coli. This study shows that cockroaches carry several Gram-negative bacteria on their body surface and alimentary tract and play a role in bacterial transmission to human. J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(2): 63-68